Identification of susceptibility pathways for the role of chromosome 15q25.1 in modifying lung cancer risk - Ji, Xuemei; Bossé, Yohan; Landi, Maria Teresa; Gui, Jiang; Xiao, Xiangjun; Qian, David; Joubert, Philippe; Lamontagne, Maxime; Li, Yafang; Gorlov, Ivan; de Biasi, Mariella; Han, Younghun; et al. (Nature communications, 2018)
Genome-wide association studies (GWAS) identified the chromosome 15q25.1 locus as a leading susceptibility region for lung cancer. However, the pathogenic pathways, through which susceptibility SNPs within chromosome 15q25.1 affects lung cancer risk, have not been explored. We analyzed three cohorts with GWAS data consisting 42,901 individuals and lung expression quantitative trait loci (eQTL) data on 409 individuals to identify and validate the underlying pathways and to investigate the combined effect of genes from the identified susceptibility pathways. The KEGG neuroactive ligand receptor interaction pathway, two Reactome pathways, and 22 Gene Ontology terms were identified and replicated to be significantly associated with lung cancer risk, with P values less than 0.05 and FDR less than 0.1. Functional annotation of eQTL analysis results showed that the neuroactive ligand receptor interaction pathway and gated channel activity were involved in lung cancer risk. These pathways provide important insights for the etiology of lung cancer. The chromosome 15q25.1 locus is a leading susceptibility region for lung cancer. Here, the authors interrogate three GWAS cohorts with 42,901 individuals to investigate potential pathological pathways such as gated channel activity and neuroactive ligand receptor interaction in lung cancer etiology.